Hedgehog-stimulated phosphorylation of the kinesin-related protein Costal2 is mediated by the serine/threonine kinase fused. - Nybakken, K.E.; Turck, C.W.; Robbins, D.J.; Bishop, J.M. (Journal of Biological Chemistry, 2002)
The Hedgehog (Hh) signaling molecule is required for the development of numerous tissues in Drosophila. Within the cell, Hh signal transduction utilizes a large protein complex consisting of the Fused (Fu), Costal2 (Cos2), and Cubitis interruptus (Ci) proteins, but the functional interactions between these proteins are still largely uncharacterized. Using a baculovirus system, we demonstrate that the serine/threonine kinase Fu phosphorylates the kinesin-like protein Cos2 when coexpressed with Cos2. Coexpression of Cos2 and a kinase-inactive version of Fu eliminates the majority of Cos2 phosphorylation. We then show that the primary Fu-induced phosphorylation site of Cos2 is serine 572, whereas serine 931 is phosphorylated to a lesser extent. Mutation of serine 572 to alanine eliminates most, but not all, specific phosphopeptides of Cos2 when coexpressed with Fu. We also demonstrate that the phosphorylation pattern of Cos2 produced by baculovirus coexpression with kinase-dead Fu is almost identical to the phosphorylation pattern of Cos2 isolated from unstimulated S2 cells. Finally, the phosphorylation pattern of Cos2 produced by baculovirus coinfection with wild-type Fu is almost identical to that of Cos2 isolated from S2 cells stimulated by Hh, indicating that phosphorylation of serines 572 and 931 is a genuine Hh signaling event. This study clarifies the unique functions of Fu and Cos2 in Hh signal transduction and identifies only the second known phosphorylation site of a kinesin-like molecule.